Assessment of vegetation cooling effect through the application of green roofs in tropical campus environment - Arabi, Roozbeh (2018)
The high temperature is deteriorated mostly due to deficiency of green spaces particularly in tropical urban environment as a result of urbanization and population increase. Tropical University campuses and other educational contexts are not an exception. As a significant part of built-up areas, roofs include a noticeable percentage of the urban area and participate extremely to the higher air temperatures in a city. Rooftop greening is an effective way to reduce the air temperature especially in sprawling modern society and consequently ameliorate the UHI effect. But the thermal performance of tropical plants in green roofs is unknown. Consequently, this study investigated the thermal performance of tropical plants as the vegetative layer in green roofs at Universiti Putra Malaysia campus in terms of plant canopy density and coverage area percentage. The hot and cool spots in the study area were determined through satellite imagery, field measurement and simulation model. Out of seventy six successful tested plant species, nine plants were chosen through the field observation. Consequently, their Leaf area indices (LAI) were measured and compared using a canopy analyser 2000. Pandanus pygmaeus with LAI=7.545 was selected as a representative plant for extensive green roofs. Mesua ferrea tree was chosen as a representative plant for intensive green roofs with almost the same LAI value. Then, seven scenarios were designed for prediction of mean air temperature during the different daytimes in the study area using ENVI-met simulation model. In the basic scenario, existing conditions without using green roofs were analysed. Then, Pandanus pygmaeus was used with a coverage area of one-third, two-third and 100 % on the roofs. The same procedure was repeated for Mesua ferrea tree. After comparing the simulation data of different scenarios, finally, the research proved that: A: the rates of cooling effects vary at different altitudes inside the urban canopy layer. B: Extensive green roofs have the optimum cooling effect on the air layer where they are located. However, the vegetative layer of both intensive and extensive green roofs cools all the air layers located between the plant canopy and the ground surface. C: the pace of air temperature reduction from one-third coverage to two-third coverage is higher than two-third coverage to 100% coverage. D: green roofs have a negligible cooling effect in the early morning. E: the intensive green roofs had a greater cooling effect than the extensive ones. Intensive green roofs with 100% coverage area can reduce the mean air temperature up to 1.21 °C during the peak hours at the pedestrian level. However, the extensive ones mitigate the air temperature at this altitude about 0.89 °C. Also, the maximum temperature reduction occurs during peak hours when the air relative humidity reaches to its minimum level about 47 percent. It is hoped that, the outputs of this research can be implemented as an auxiliary guideline in choosing the types of vegetative layer and their coverage area in green roofs.